2019
DOI: 10.3390/ijerph16061030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physicochemical Characteristics in Drinking Water Sources Emphasized on Fluoride: A Case Study of Yancheng, China

Abstract: In this study, the concentration of fluoride and the associated health risks for infants, children, and adults were analyzed and compared for three drinking water sources in Yancheng City, Jiangsu Province, China. To analyze the relationship between the water quality parameters of pH, fluoride (F−), sulfate (SO42−), chloride (Cl−), total dissolved solids (TDS), total alkalinity (TAlk), sodium (Na+), and potassium (K+), statistical analyses including correlation analysis, R-mode cluster analysis and factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Thus, a strong correlation was found between sodium and chloride ions in fluoridated groundwater which showed saline condition and this observation is well supported by other studies. 11,44 Moreover, higher F − dissolution in groundwater is due to silicate weathering under alkaline conditions in the lower Gangetic plain which is supported by other studies. 11,45 Collected fluoridated groundwater samples from the studied areas were verified for physicochemical analyses and ionic concentration assessments of the estimated data.…”
Section: Resultsmentioning
confidence: 53%
“…Thus, a strong correlation was found between sodium and chloride ions in fluoridated groundwater which showed saline condition and this observation is well supported by other studies. 11,44 Moreover, higher F − dissolution in groundwater is due to silicate weathering under alkaline conditions in the lower Gangetic plain which is supported by other studies. 11,45 Collected fluoridated groundwater samples from the studied areas were verified for physicochemical analyses and ionic concentration assessments of the estimated data.…”
Section: Resultsmentioning
confidence: 53%
“…Therefore, in the case of caries prevention, an additional supply of fluoride is needed. On the other hand, in the case of too much fluoride content in the consumed water, bottled water can be an alternative way to reduce the supply of fluoride to the body [ 49 , 50 , 51 ].…”
Section: Sources Of Fluoridementioning
confidence: 99%
“…In the Dejiala River values of Sulphate ions ranged from 40 to 150 mg l -1 [61]. Also, the mean values of sulphate ions in Tongyu River and Mangshe River were 49 and 43 mg/L, respectively [62]. Rashad et al [63] observed the mean value of sulphate ions of Nile River ranged from 26.5 mg l -1 in winter to 24 mg l -1 in summer.…”
Section: Sulphate ‫۽܁(‬ ି )mentioning
confidence: 99%